The Australian Matildas at FIFA 2023: spurring social change, sports policy and soft power diplomacy - Kampmark, B. (Soccer & Society, 2026)
Beyond expectations, the host side in the 2023 FIFA Women`s World Cup, held in Australia, reached the semi-finals, only to lose to the European champions, England. This article considers the growing influence of the Matildas (Australian national women`s football team), the enormous challenges that have faced women competitors in football/soccer in Australia, the legacy of the team`s performance at the tournament, and what prospects this offers the game in Australian women`s sports at the community, club and elite level. The catalytic changes effected by the Matildas on female participation and roles in sporting endeavours and beyond, helped by their increasing marketability and visibility, are examined. Mention is also made of government policies capitalizing on the `Matilda effect` in social policy and soft power diplomacy. This paper also considers the continuing challenges facing the Matildas and female soccer in the country, including persistent scepticism about the value of women`s sports.